Disrupsi sebagai Era Baru Penuh Kejutan: Tinjauan Filsafat Teknologi Terhadap Fenomena Disrupsi - Sabar, Fransiskus (Universitas Insan Budi Utomo, 2025)
In its development, technology has consistently surprised human life. One of them is the phenomenon of disruption, which is a direct offspring of technology itself. Disruption is the change that “disturbs,” “shakes,” and “uproots” something from it something from its foundation. In other terms, the presence of this disruption has drastically altered human life. It “disturbs” business practices while also “changing” the systems of knowledge distribution or education, altering human interactions, societal character, and transforming daily human life. Utilising a philosophical approach to technology in facing the current technological disruption era that is striking the order of human life is a highly relevant academic step. Philosophy, with its tradition of critical-systematic and emancipatory thinking, is deemed capable of fending off the storm of disruption that disturbs the order of human life. The destructive effects if disruption such as misinformation, the conquest of incumbent groups by start-ups, the demise of expertise, the blind glorification of technology and the collapse of local wisdom are tangible evidence of the dangers of the disruption era that must be faced wisely. This technological philosophical approach may assist in clearly mapping the positive and negative impacts of the disruption phenomenon.